THE ROLE OF THE COMMUNITY AND THE QUALITY OF VILLAGE REGULATIONS - Novia Ayu Permatasari; Adhitya Widya Kartika (UNTAG Law Review, 2019)
Society is one of the elements in the formation of legal products by the government so that the legal products that are formed do not cause harm to one or both parties. Formation of legal products or laws and regulations in order to meet legal objectives (for example justice, expediency, and legal certainty), it is also necessary that a legal product is made by an authorized official or government which by law is given the authority to form regulations laws or legal products. This is important because it relates to the relief of a legal product or the needs and issues of village law between one village and another because of the different environmental and community conditions between one village and another. Community participation in the formation of village regulations is important because the community knows about legal issues in the community, so it is important when establishing laws and regulations, especially villageregulations to find out the aspirations of the village community concerned. In addition, public legal awareness is important in the context of enactment to achieve the goals of what is the goal of a legal product that is made. The method used is a normative juridical approach to the legislation and the doctrine of law and using qualitative analysis.